ETHICAL LEADERSHIP AND INTEGRITY: ANALYTICAL STUDY OF LEADERSHIP VALUES IN ISLAMIC BOARDING SCHOOL - Ahmad Junaidi; Abdul Aziz Abdul Aziz; Nur Efendi Nur Efendi (As-Sulthan Journal of Education, 2026)
This study aims to analyze ethical values and integrity of leadership at tAl-Muntaha Al-Cholily Islamic Boarding School, Jengkebuan-Bangkalan. This study uses a qualitative descriptive method with a case study approach. Research data were obtained through observation, interviews, and documentation, which were analyzed using Miles and Huberman approach. This analysis consists of three stages: data reduction, data presentation, and conclusion drawing. The results show that ethical leadership and integrity at the Al-Muntaha Al-Cholily Islamic Boarding School Jengkebuan-Bangkalan are manifested in several activities such as making teachers as a partners in formulating policies, proportionality in providing attention, delegating tasks, providing examples of discipline, moral habits, enforcing rules, strengthening character through regular teacher religious studies, discipline in administration and reporting, and so on. These indicators are relevant to Michael E. Brown and Marie S. Mitchell and Gary Yukl theory that ethical leaders can be identified, among others, through their honest, trustworthy personalities and reflecting strong religiosity